Do Be Afraid: Folk Horror, Monstrous Sacred and Divine Terror in The Silt Verses Podcast - Kobus, Aldona (Literatura Ludowa. Journal of Folklore and Popular Culture, 2025)
The article analyzes contemporary folk horror podcast series The Silt Verses (2021–ongoing) in order to theorize how horror as a genre conveys the relationship with the sacred in contemporary culture, with the characteristics and functions of the sacred described by Roger Caillois in L’homme et le sacré. First, the article focuses on the folk horror aspect of the series, how it alters the sub-genre conventions and how it presents the monstrous sacred which leads to notion of “divine terror” or “sacred dread” and fear as a primordial response to the sacred and, therefore, the role of religious horror as reminiscent of the religious experience within contemporary society. Lastly, the article will argue that the interchangeability of the sacred and capitalism within the fictional world of the podcast poses the question of what has taken the place of the sacred in the contemporary culture and points at the inviolable status of the capitalistic economy, in the name of which we commit contemporary human sacrifices.